Comparison Of Dividend Policy, Profitability And Company Value Before And During The Covid-19 Pandemic - Iqbal Afif Amrullah; Diyah Probowulan; Rendy Mirwan Aspirandi (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
This study is find out if there is a difference between the Dividend Policy, Profitability, and Company Value before and during the covid-19 pandemic. The object of this research is a company that is incorporated in the Indonesia Stock Exchange. The data analysis technique used is descriptive analysis   After that, different tests were carried out to find out whether there were significant differences in the variables to be tested. The final result in the test is that the value of The Return On Asset test shows that there is a significant difference between before the pandemic and during the Covid-19 pandemic. The Price to Book Value test can be stated to have a significant difference.